Implications of the EU Regulation on Public Oversight Systems for Statutory Auditors - Ana Gisbert; Begoña Navallas; Pablo Gómez-Carrasco; Elena de las Heras (Revista de Contabilidad: Spanish Accounting Review)
Audit oversight plays a crucial role in ensuring audit quality. Despite recent progress in strengthening public audit oversight systems in Europe, in this paper we address the issues where little harmonisation has been achieved. Based on the content of the European Directives, we show how significant differences still exist and affect the EU system of public audit oversight. We examine the supervisory and disciplinary functions, organisational structure, funding and transparency mechanisms of the main public oversight bodies in the EU, Australia, the UK and the EEUU. The analysis suggests that despite the common framework set out in EU directives and regulations, the current system of public oversight in Europe is still far from achieving a reasonable degree of harmonisation, which hampers the effectiveness of audit oversight bodies. We contribute by providing an institutional framework that allows to identify the impact of the most adopted features on the independence and competence of each oversight body.